Neonatal Seizures: Correlation between Clinico-Etiological Profile and EEG Findings (Bangladesh Journal of Child Health, 2014)
Introduction: Seizures are quite common in newborn babies. Among other investigations, EEG is used to show the type and location of the activity in the brain during a seizure. Correlation between clinico-etiological profile of neonatal seizures and EEG findings, so far, has not been studied in Bangladesh. Objective: The objective of the study was to correlate the clinical, etiological and EEG profile of neonatal seizures. Methodology: It was a cross-sectional study done at NICU of BSMMU and Central Hospital Ltd. All the neonates admitted with seizures during the study period were included in the study. Their clinico-etiological profiles were carefully recorded and EEG were done in all the cases. Chi-square test was done to find out the statistical difference. Results: Among total 51 cases of neonatal seizures, 29 (56.86%) cases had perinatal asphyxia, followed by septicemia in 8 (15.67%) and meningitis in 6 (11.76%). Hypoglycemia and hypocalcaemia was found in 10 (19.6%) & 8 (15.7%) cases respectively and 15 (29.4%) had acidosis. Thirty seven (72.5%) patients had seizure within 3rd day of life. Seizures were found tonic in nature in 23(45.1%) cases and subtle 18 (35.3%) cases. EEG findings were abnormal in 22 (43.1%) cases. EEG findings were analyzed with the etiology of seizures and it was found that there was a significant relationship between EEG changes and perinatal asphyxia (p